Psychologically impacted houses - superstitions and marketability problems - Alias, A.; Hamsani, D.F.; S.J.L., Chua; Zaid, S.M. (Penerbit UKM, 2014)
Psychologically impacted houses may be a new context in Malaysia but the term psychological impacted or defects have been distinguished in the United States and Australia. With the increases of wrongdoing these days, there is a possibility that the crime will result in death in a house. This paper focused on the issues of psychologically impacted houses with respect to the discernment of the society towards these houses and the problems in marketing these tainted properties. A study is carried out to acquire the data on the level of superstitious convictions that are still practiced by the Malaysian society. The relationship between superstition and psychologically impacted houses are being discussed as the perception of the society towards the stigmatized houses is clouded by their superstitious beliefs. The issues in regards to the marketability of psychologically impacted houses are highlighted through the findings obtained from interviews with estate agents and negotiators. Thus, the main aim of this paper is to ascertain the dilemma faced by estate agents and negotiators when marketing houses with psychological defects. Recommendations are made to help the estate agents and negotiators to see things clear with respect to the disclosure of information of the houses.